DETERMINATION SHELL THICKNESS AND STRESS ANALYSIS OF PIG LAUNCHER AND PIG RECEIVER IN GAS TRANSMISSION SYSTEM - Iqbal Firdaus, Muhammad
In every gas transmission system there is a Pigging whose main function is to clean the gas transmission system and also inspect the damage of the gas distribution pipe. The tools used to perform Pigging are Pig Launcher and Pig Receiver. Pig Launcher and Pig Receiver work by inserting Pig into the barrel of Pig Launcher and Pig Receiver. In this study, the author will conduct an analysis to determine the thickness for the Pig Launcher and Pig Receiver. In addition, stress analysis to calculate the stress received by the Pig Launcher and Pig Receiver. The analysis was carried out on Pig Launcher and Pig Receiver with API 5L X52 and ASTM A106 Grade B materials. Prior to analysis, models of barrels and Pig Receiver need to be made using Computer-Aided Design (CAD) software. Analysis with calculation was carried out based on ASME B31.8 and ASME.BPVC.VIII.1. Analysis with numerical methods was conducted using finite element methods that were visualized with finite element analysis software. Through this study, it was found that the thickness calculation and stress analysis had met the stress limits applied by ASME B31.8 and ASME.BPVC.VIII.1. The thickness calculation analytically has also been validated using stress analysis so that the value of the thickness of the barrels, both major barrels and minor barrels from Pig Launcher and Pig Receiver, can be accepted.